Single-Molecule Sensitivity in Optical Absorption at Room Temperature - Kukura, P; Celebrano, M; Renn, A; Sandoghdar, V (2010)
Sensitive detection of condensed matter is of utmost importance in fundamental research as well as cutting-edge applications such as molecular analytics and diagnostics. Until very recently, all existing methods for the detection of single molecules at room temperature have required highly efficient fluorophores. Here, we demonstrate, for the first time, that single molecules can also be detected via standard modulation-free absorption measurements. Our work extends single-molecule detection to a huge class of materials that absorb light but do not fluoresce efficiently. © 2010 American Chemical Society.